#TITLE_ALTERNATIVE# - SAFITRI (NIM: 22310303); Pembimbing : Wahyu Triyoso, Ph.D, VERINA
Utilization of 2D seismic data, in case the data consists of some vintage with differences in acquisition parameters and data processing, would lead to differences in amplitude and bandwidth on each vintage. In addition, the use of geostatistical analysis methods on 2D seismic data to map the geometry of a rock layers and geological structures in the subsurface as well as the distribution of attributes would not be optimal if the seismic data has sparse location between each other. To solve the problem of differences in amplitude and bandwidth from different vintage, it is necessary to process the seismic data using the same parameters. Then, by utilizing the method of Partial CRS Stack, it is expected to produce a better subsurface section than the conventional methods. And to overcome the limitations of 2D seismic data in geological modeling, geostatistical analysis was performed to distribute the rock properties which is the output from seismic inversion to obtain the distribution of rock properties in 3-dimensional geometry, and then we can create a pseudo3D seismic from derivative of that properties.The pseudo3D seismic then used as an input in the seismic attributes analysis. From the results of the sweetness attribute distribution using 2D seismic data and pseudo3D seismic showed a relatively similar trend. However, the distribution of relatively high sweetness attribute value of seismic pseudo3D is smaller than the distribution from 2D seismic.